A novel whole blood assay to quantify the release of T cell associated cytokines in response to Bordetella pertussis antigens - Mills, Kingston (My University, 2024)
Background: Bordetella pertussis continues to cause whooping cough globally even in countries with high immunisation coverage. Booster vaccinations with acellular pertussis vaccines are thus used in children, adolescents, and adults. T cell immunity is crucial for orchestrating the immune response after vaccination. However, T cell assays can be expensive and difficult to implement in large clinical trials. In this study, a whole blood (WB) stimulation assay was developed to identify secreted T cell associated cytokines in different age groups after acellular pertussis booster vaccination. Material and methods: Longitudinal WB samples were collected from a small set of subjects (n = 38) aged 7–70 years participating in a larger ongoing clinical trial. For assay development, samples were diluted and incubated with purified inactivated pertussis toxin (PT), filamentous haemagglutinin (FHA), inactivated B. pertussis lysate, and complete medium (M) as stimulating conditions, with anti-CD28 and anti-CD49d as co-stimulants. Different timepoints around the vaccination (D0, D7, D14, D28), WB dilution factor (1:2, 1:4) and incubation time (24 h, 48 h, 72 h) were compared. Responses to 15 cytokines were tested with Luminex/multiplex immunoassay. Results: The optimized assay consisted of WB incubation with M, PT, and FHA (including the two co-stimulants). After 48 h incubation, supernatants were collected for measurement of seven selected T cell associated cytokines (IL-2, IL-5, IL-10, IL-13, IL-17 A, IL-17F, and IFN-y) from samples before and 28 days after vaccination. PT stimulation showed a trend for upregulation of IL-2, IL-13, and IL-17 A/F for adult subjects, whereas the responses of all cytokines were downregulated for the paediatric subjects. Furthermore, PT and FHA-stimulated WB showed diverse cytokine producing profiles. Conclusions: The developed WB-based cytokine assay was shown to be less costly, easy to perform, and functional in differently aged individuals. Further, it requires only a small amount of fresh blood, which is beneficial especially for studies including infants. Our results support the use of this assay for other immunological studies in the future.
PUBLISHED
cited By 0
Keywords: Bordetella pertussis; Cytokines; Filamentous hemagglutinin; Pertussis toxin; Vaccination; Whole blood